The Great Carbon Arbitrage - Adrian, Tobias (IMF Working Papers; Working Paper ;, 2022)
We measure the gains from phasing out coal as the social cost of carbon times the quantity of avoided emissions. By comparing the present value of the benefits from avoided emissions against the present value of costs of ending coal plus the costs of replacing it with renewable energy, our baseline estimate is that the world can realize a net gain of 77.89 trillion USD. This represents around 1.2% of current world GDP every year until 2100. The net benefits from ending coal are so large that renewed efforts, carbon pricing, and other financing policies we discuss, should be pursued.